Fabrication of silver-nanoparticles-embedded polymer masterbatchs with excellent antibacterial performance - Hang, Trinh Thi; Tam, Phuong Dinh; Huy, Tran Quang; Tuan, Le Anh (Vietnam Journal of Chemistry, 2014)
In the present work, a versatile and effective synthesis method of the silver-nanoparticles-embedded polyethylene (PE)-based polymer masterbatchs was demonstrated. Antibacterial investigations revealed that the nano-silver masterbatchs consisting of oleate capped silver nanoparticles dispersed in PE polymer matrix exhibited excellent antibacterial performance against Gram-negative Escherichia Coli (E.coli) and Staphylococcus aureus (S. aureus) bacteria.  A complete inhibition in bacteria growth was found at a silver nanoparticles concentration as low as 600 ppm. The origin of bactericidal effect and interaction mechanism of the stabilized silver nanoparticles with the Gram-negative E. coli and Gram-positive S. aureus bacteria can be understood in the light of electron microscopic observation. These advances make the synthesized nano-silver masterbatchs ideal for mass production of effectively antibacterial green products in medical, biological and industrial sectors. The type of polymer resin and silver concentration can be adjusted depending on the application area.